UJI AKTIVITAS ANTIBAKTERI SEDIAAN MASKER GEL EKSTRAK DAUN TAPAK DARA (Catharanthus roseus (L) G. Don) TERHADAP BAKTERI Staphylococcus aureus - Agustina, Isnaini; Wardani, Tatiana Siska; Luthfiyanti, Niken (Universitas Imelda Medan, 2025)
Gel masks are semi-solid preparations that serve as skincare products with benefits, such as addressing various skin problems. This study aims to conduct a physical quality test on gel masks containing tapak dara leaf extract, determine the antibacterial activity of tapak dara leaf extract and evaluate the antibacterial activity of the tapak dara leaf extract gel mask against Staphylococcus aureus ATCC 25923 bacteria. This study uses both qualitative and quantitative analysis with experimental methods. The extraction of virgin leaves is carried out using the maceration method with a 70% ethanol solvent. The extracts and preparations are made into three concentrations: 10%, 20%, and 30%. The physical quality testing of tapak dara leaf gel masks includes organoleptic evaluation, homogeneity, pH, dispersion, and drying time. The results of one-way ANOVA for pH (sig. = 0.815), dispersion (sig. = 0.695), and drying time (sig. = 0.251) showed that the significance values were greater than 0.05. Tapak dara leaf extract demonstrates antibacterial activity against Staphylococcus aureus bacteria, with inhibitory zone diameters of 3.5 mm, 7.87 mm, and 9.85 mm. The gel mask preparation of virgin palm leaf extract exhibits antibacterial activity against Staphylococcus aureus bacteria, with inhibition zone diameters of 3.67 mm, 4.77 mm, and 7.4 mm. The results of one-way ANOVA on the activity of virgin palm leaf extract against Staphylococcus aureus bacteria showed a significance value less than 0.05.